The Role of Microbiota and Early Detection in Colorectal Cancer Through Fecal Screening - Iqbal, Muhammad (Faculty of Medicine, Universitas Andalas, 2024)
Objective: This literature review explores the link between gut microbiota and colorectal cancer, emphasizing early detection through fecal screening. Method: We conducted a comprehensive literature review, using Google Scholar and PubMed, with key search terms including